Personal information disclosure under competition for benefits: Is sharing caring? - Viola Ackfeld; Werner Güth (Max Planck Institute for Research on Collective Goods, 2019)
Personal information is shared extensively every day, partly in exchange for benefits or as a reaction to other people's information sharing. In this paper, we experimentally investigate these two factors by analyzing the interaction of peer comparison and incentives to disclose potentially privacy-sensitive information. We find that information sharing is higher under incentives, and further increases under peer comparison. This effect is driven by those initially disclosing less, who additionally report to feel more compelled to reveal information. Our results provide an explanation for the current information sharing trend while pointing to a potentially neglected side-effect.
Keywords: C92; D30; D82; 330; Personal information disclosure; Peer comparison; Incentives; Experiment